Field measurements within a quarter of a city including a street canyon to produce a validation data set. (1st September 2005) - Schafer, Klaus; Emeis, Stefan; Hoffmann, Herbert; Jahn, Carsten; Muller, Wolfgang; Heits, Bernd; Haase, Dirk; Drunkenmolle, Wolf-Dieter; Bachlin, Wolfgang; Schlunzen, K.; Leitl, Bernd; Paschek, Frauke; et al.
Air pollutants and meteorological parameters were measured continuously by in situ instruments, path-averaging techniques (up to three DOAS systems), and SODAR inside a street canyon and in the surrounding area of 1 km x 1 km (Gottinger Strasse in Hanover, Germany) from 2001 until 2003 which are available in the data bank ValiData for validation of microscale models. During three IOPs tracer experiments with a SF6 line source, sampling techniques of up to 15 sites and path-averaging FTIR spectrometry were performed. Concentration measurement results at roof level were anti-correlated with SODAR mixing layer heights, while those inside the street canyon are not. Re-circulation flow patterns inside the street canyon were studied together with corresponding wind tunnel experiments.